Clinical characteristics, treatment and prognosis of children with SARS-CoV-2 infection complicated with severe neurological dysfunctions in Foshan, China - Xiaoqian Chen; Yongqi Liang; Suhua Jiang (Frontiers Media S.A., 2024)
ObjectiveTo analyze the clinical characteristics, treatment, and prognosis of children infected with SARS-CoV-2 following the adjustment of COVID-19 prevention and control policies in China in December 2022.MethodsA retrospective study was conducted on 9 cases of severe neurological dysfunction caused by SARS-CoV-2 infection in children admitted to Foshan First People's Hospital from December 17 to 31, 2022.ResultsAmong the 9 cases, 7 (71.43%) were under 3 years old, and 2 (22.2%) were over 3 years old with underlying diseases. All patients presented with fever and neurological symptoms such as consciousness disturbance and/or convulsions, and their conditions deteriorated rapidly within 24 h after the onset of fever, without respiratory symptoms. Levels of IL-6, LDH, and d-dimer were significantly elevated. Five cases died within 48 h of admission, one case died after 7 days of treatment due to secondary bacterial infection, and three cases survived for more than 48 h after the initial rescue. All patients developed rapid shock, and five cases experienced multi-organ failure within a short period. In terms of treatment, glucocorticoids were used in 5 cases, intravenous immunoglobulin (IVIG) in 3 cases, and blood purification and tocilizumab in 2 cases.ConclusionSARS-CoV-2 infection in children can lead to severe neurological damage. High fever, convulsions, and inflammatory factors serve as early warning indicators. Glucocorticoids, immunoglobulins, blood purification, and tocilizumab may have some therapeutic effects, but further research is needed to confirm the efficacy.